A Holy People : Jewish and Christian Perspectives on Religious Communal Identity - Poorthuis, Marcel; Schwartz, Joshua J. (Jewish and Christian Perspectives Series, 2006)
A Holy People investigates the various ways in which Jews and Christians define their religious identity, people or community, as being holy. Keeping in mind that historical studies can offer food for thought regarding contemporary issues, the study offers a large collection of essays, relating to the biblical, patristic and medieval period and especially to the modern period. The obvious question of many in the modern world as to whether the attribute of the 'holiness' allows for acknowledgement of authentic religion outside the own religious community, deserves an honest answer and well-documented study: too easily the claim of holiness intertwines with claims of power, whether by rivalling groups within the religious community, by groups divided along gender lines, or on the level of territorial claims. It will be of special importance to scholars and general readers interested in an interdisciplinary approach to theology, rabbinics, history, political science, and much more.